Combined efficiency of salicylic acid and calcium on the antioxidative defense system in two different carbon-fixative turfgrasses under combined drought and salinity - Torun, Hülya (South African journal of botany, 2022)
•Combined stress reduced activities of SOD, POX, APX and GR in perennial ryegrass, but solely GR in Bermuda grass.•Combined stress deleterious effects were more pronounced in Bermuda grass in terms of TBARS and H2O2 accumulation.•Simultaneous application of SA+Ca can play positive regulatory role under combined drought and salinity.•SA+Ca modulated drought+salt-induced damage in growth parameters and K, Mg and Ca accumulation in Bermuda grass.•Antioxidant defense system in perennial ryegrass was strengthened by SA+Ca under combined stress. Combined stress effects are unique when compared to individual stress applications. As the subject has not been previously examined, the aim of this study was to investigate the role of salicylic acid (SA) and calcium (Ca) as signaling molecules under combined drought and salt stresses on two different carbon-fixative turfgrasses, Lolium perenne L. (perennial ryegrass; C3) and Cynodon dactylon (L.) Pers. (Bermuda grass; C4). Twenty-one days after germination, PEG6000 (5%) and NaCl (150 mM) were applied simultaneously as a combined drought and salinity (DS) treatment. Before starting the treatment, half of the seedlings were treated with SA (0.5 mM) solution for 24 h; Ca (5 mM) was also applied simultaneously to the SA-treated groups. Combined drought and salt stresses caused substantial decreases in leaf growth parameters, relative water content, and osmotic potential in both cultivars, whereas lipid peroxidation (TBARS), hydrogen peroxide (H2O2), and electrolyte leakage increased. However, the deleterious effect of the combined stress was much more pronounced in Bermuda grass. On the other hand, activities of superoxide dismutase (SOD), peroxidase (POX), ascorbate peroxidase (APX), and glutathione reductase (GR) in perennial ryegrass and only GR in Bermuda grass were reduced by DS. Moreover, Na accumulation was greater in perennial ryegrass (33.9-fold) than in Bermuda grass (11.1-fold). Under stress, simultaneous SA+Ca application was more effective on the recovery potential of Bermuda grass than on that of perennial ryegrass, with enhanced growth as well as increased proline, K, Mg, and Ca contents, and retained RWC. However, the SA+Ca treatment for the perennial ryegrass under DS significantly enhanced the antioxidant defense activities of SOD, POX, APX, and GR as well as increasing the TBARS and H2O2 content, compared with plants subjected to DS alone. Taken together, these results indicated that simultaneous application of SA+Ca could play a positive regulatory role, which in turn could improve the double-stress tolerance of turfgrasses.